Globalization of Ambitions. A Critical Analysis of Donald Trump’s National Security Strategy 2017 - N. P. Gribin (Международная аналитика)
Under the Goldwater-Nichols Defense Department Reorganization Act of 1986, the President of the United States must submit to Congress each year a report on the national security strategy. This report under the name of “National Security Strategy” is intended to be a comprehensive statement anticipating the worldwide interests, goals and objectives that are deemed crucial to the national security of the United States. The new “National Security Strategy” (December 2017) lays out the strategic vision of the Presidential Administration under Donald Trump about ways and means by which the US seeks to deal with internal and external threats. The authors of the Strategy set themselves the main task of proving that American security is based on the realization that American principles are: “a lasting force for good in the World.”  The authors of the Strategy prioritize the protection of the American way of life and American interests all over the world. In that aspect, they see the main danger from the hostile states and non-states actors who are “trying to acquire different types of weapons”. In addition, the administration is demonstrating concerns about the activity of international terrorist organizations (jihadist), transnational criminal organizations, drug cartels and cybercrime. Different from previous similar documents, Trump’s Strategy makes an evident accent on economic security as an important part of national security. The task in that area is “to rebuild economic strength at home and preserve a fair and reciprocal international system.” In a rather confronting manner, the Strategy assesses the role of China and Russia in the international affairs. It underlines that between the main sets of challengers – “the revisionist powers of China and Russia and the rogue states of Iran and North Korea”, the United States will seek areas of cooperation with competitors but will do so from a position of strength. The Strategy pays great attention to restoring military capability of the US. It is stressed that military strength remains a vital component of the competition for influence. In a certain sense, the authors of the Strategy demonstrate a new approach to the role of diplomacy, and especially in regards to the tools of economic diplomacy, intended to protect the US “from abuse by illicit actors”. Pillar four of the Strategy outlines considerations for expanding US influence on a global scale and for supporting friendly partners. As stated in the Strategy, American assistance to developing countries should help promote national interests and vice versa. The US will use all means, including sanctions, to “isolate states and leaders that pose a threat to the American interests.” The Strategy pays much attention to the regional aspect of national security, and, from these positions, the situation in various parts of the world (the Indo-Pacific region, Europe, the Middle East, etc.) is assessed. The authors emphasize that changes in the balance of power at the world level can cause global consequences and threaten American interests and US security. On the contrary, “stability reduces the threats that Americans face at home.”